How to link people, government, and science in effective large-scale management of invasive trees - Sprague, R.; Hulme, P. E.; Nuñez, M. A.; Peltzer, D. A. (Frontiers in Environmental Science, 2022)
A common limitation for the effective management of widespread non-native species is translating and implementing the latest scientific knowledge for practitioners. Non-native tree invasions are no exception to this problem. We illustrate how the National Wilding Conifer Control Programme in New Zealand has worked to overcome these limitations through a partnership approach, ensuring affected communities are connected to on-the-ground responses, and facilitating the transfer of new scientific knowledge to practitioners. By ensuring the overarching management strategy was developed collaboratively with clear, mutually-agreed goals, the programme has helped to unite diverse stakeholders with a common purpose. Although coordinated by a central government body, the governance structure is sufficiently flexible to address the specific management needs of each affected community. The programme takes an adaptive management approach that enables multiple lines of research and management to be developed together; this was essential to improve management across different regions and stages of invasion. A co-developed strategy, partnership structure, and adaptive management were each critical components of the National Wilding Conifer Control Programme. However, there are ongoing challenges to overcome, such as securing long-term funding and reducing risks of re-invasion, to meet the ultimate goal of containing conifer invasions nationally. We suggest that lessons from this programme provide general insights into how linking people, government, and science could be used to improve the effectiveness of large-scale invasive non-native species management elsewhere.